1980
DOI: 10.1007/bf02774306
|View full text |Cite
|
Sign up to set email alerts
|

Ten year survival rate of 131 patients with liver cirrhosis excluded the association of liver carcinoma at the establishment of diagnosis

Abstract: The present study reported 10 year suvival rate of 131 patients with liver cirrhosis excluded the association of liver carcinoma. Survival rate was calculated according to the life table method of Cutler and Ederer. One hundred thirty-one patients were diagnosed between 1965 and 1972. The overall 5 and 10 year survival rates of 131 patients were 58.3 +/- 4.7% and 36.5 +/- 6.2%, respectively. The 5 and 10 year survival rates of 56 patients with decompensated liver cirrhosis were 32.9 +/- 6.9% and 19.0 +/- 6.9%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…Strict etiological classification among LC patients may become possible with the development of detection of the non-A, non-B hepatitis virus. The 5-year survival rate of LC patients was 62% in this study, 5&70% collectively in the collection (8), 55% (17) and 58% (18) in recent Japanese studies, 30% (16) in an English study and 5% (3) in an earlier Japanese study. The 10-year survival rate was 42% in this study, 36% (17) and 37% (18) in recent Japanese studies and 20% (16) in an English study.…”
Section: Increase Of Lc Patientssupporting
confidence: 47%
“…Strict etiological classification among LC patients may become possible with the development of detection of the non-A, non-B hepatitis virus. The 5-year survival rate of LC patients was 62% in this study, 5&70% collectively in the collection (8), 55% (17) and 58% (18) in recent Japanese studies, 30% (16) in an English study and 5% (3) in an earlier Japanese study. The 10-year survival rate was 42% in this study, 36% (17) and 37% (18) in recent Japanese studies and 20% (16) in an English study.…”
Section: Increase Of Lc Patientssupporting
confidence: 47%
“…In the same study, 19 patients died within the first 2 years of follow up, giving an annual mortality rate of 9.9%, 48 with a corresponding 5‐year mortality rate of 41%, compared with the mortality rate of 67% reported by a Japanese study involving 56 patients with decompensated cirrhosis 46 . In the latter study, the estimated annual mortality rate was 20%.…”
Section: Resultsmentioning
confidence: 83%
“…Seven studies were identified reporting mortality rates among patients with cirrhosis 29,39 , 40,43 , 45–47 . The annual mortality rates derived from major studies were between 3.1 and 8.0%.…”
Section: Resultsmentioning
confidence: 99%
“…Observational cohort studies of compensated cirrhosis that were reported in the English language included the following: diseased populations evaluated at tertiary referral centers, study periods between the years 1958 and 1990, predominant hepatic disease etiologies including alcohol and chronic viral hepatitis, and patient follow-up rates greater than 80%. 3 From reported investigations of large cohorts, [4][5][6][7][8][9][10][11][12][13][14][15][16][17] the median survival of patients with compensated cirrhosis is estimated at between 7 and 10 years from the time of diagnosis. Nearly 100% of individuals affected by compensated cirrhosis from chronic viral hepatitis can expect to survive at least 2 to 5 years after diagnosis 7,9,[13][14][15][16][17] (Figure 1).…”
Section: Natural History and Prognosis Compensated Cirrhosismentioning
confidence: 99%